Pengembangan Model Kurikulum Berbasis Cinta dan Ekoteologi di Madrasah Pendekatan Design-Based Research - Subekhi, Khomad; Mukh. Nursikin (Yayasan Literasi Altruis Khatulistiwa, 2025)
Developing a curriculum that addresses the moral and ecological crisis is urgent in contemporary Islamic education. This study aims to develop a Love-Based and Ecotheology-Based Curriculum Model in Madrasah/PTKIN through a Design-Based Research (DBR) approach that includes needs analysis, design, implementation, and iterative evaluation. Love values ​​such as empathy and caring as well as ecotheology values ​​based on the principles of caliph and trust are integrated as the basis of the curriculum. Data were collected through observation, interviews, FGD (Focus Group Discussion), and document analysis. The results of the study showed an increase in empathy, positive interactions, spiritual reflection, and ecological awareness of students after the implementation of this model. Teachers also felt that learning became more humanistic and contextual with environmental issues. However, teacher readiness and limited teaching materials and institutional support remain challenges to implementation. This study concludes that the integration of love and ecotheology values ​​can be a relevant and transformative curriculum model for Islamic education, while also providing theoretical and practical contributions to the development of a spiritual-ecological curriculum